Paragonimus westermani as a cause of Löeffler's syndrome - Satoshi Furuya; Sayato Fukui; Yoichiro Maekawa; Nozomi Aoki; Akihiro Inui; Toshio Naito (IDCases, 2022)
In 1936, Löeffler first recognized the association between a distinctive form of severe heart failure and marked eosinophilia. Most cases are caused by either parasitic infections or drugs; however, no cause has been identified in one-third of the patients [1]. This report presents a rare case of Löeffler’s syndrome caused by the parasite Paragonimus westermani.